2021
DOI: 10.3389/fpls.2021.768963
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Cultivation Area of Pecan (Carya illinoinensis) Toward the South in Southeastern Subtropical China May Cause Increased Cold Damage

Abstract: Pecan (Carya illinoinensis) is an important nut tree species in its native areas in temperate and subtropical North America, and as an introduced crop in subtropical southeastern China as well. We used process-based modeling to assess the effects of climatic warming in southeastern China on the leaf-out phenology of pecan seedlings and the subsequent risk of “false springs,” i.e., damage caused by low temperatures occurring as a result of prematurely leafing out. In order to maximize the biological realism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Nanping is located in the north of Fujian province; mountainous areas and hills are widely distributed in the subtropical humid monsoon climate. It has jurisdiction over two municipal districts, five counties, and three county-level cities, covering an area of 26,300 square kilometers, ranging from 117°00 'E to 119°25' E and from 26°30 'N to 28°20' N [ 14 , 18 , 19 ]. In recent years, the People's Government of Nanping City has actively responded to national policies and vigorously carried out ecological civilization construction, such as restoring forests and wetlands, banning the traditional burning of straw in rural areas, and reducing industrial land use.…”
Section: Discussionmentioning
confidence: 99%
“…Nanping is located in the north of Fujian province; mountainous areas and hills are widely distributed in the subtropical humid monsoon climate. It has jurisdiction over two municipal districts, five counties, and three county-level cities, covering an area of 26,300 square kilometers, ranging from 117°00 'E to 119°25' E and from 26°30 'N to 28°20' N [ 14 , 18 , 19 ]. In recent years, the People's Government of Nanping City has actively responded to national policies and vigorously carried out ecological civilization construction, such as restoring forests and wetlands, banning the traditional burning of straw in rural areas, and reducing industrial land use.…”
Section: Discussionmentioning
confidence: 99%
“… Pletsers et al (2015) also found that the budburst time of two tree species ( Betula pubescens and Populus tremula ) was earlier with the increase in the CA. The controlled experiment not only could directly reflect the effect of chilling on spring phenology, but also could help to develop biologically realistic process-based models of spring phenology in trees if the experiments were explicitly designed for describing the temperature responses of the simulated processes (e.g., Zheng et al, 2021 ; Zhang et al, 2022 ). Long-term observations also showed consistent results with the controlled experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to effects of chilling on endodormancy release, these models also address the effects of high temperatures on ecodormancy release, thus predicting the timing of spring phenological events such as leafout of leaf buds and the flowering of flower buds (Figure 1). Today, process-based tree spring phenology models are major tools in global change studies where the ecological effects of climatic change are evaluated (Wang et al, 2020;Zheng et al, 2021). This is because changes in phenology have several important implications at the ecosystem level, such as changes in the cycling of nutrients, carbon, and water, or changes in the trees' relationships with herbivores (Kramer and Hänninen, 2009;Richardson et al, 2009;Senior et al, 2020).…”
Section: Process-based Phenology Modelling Quantifying the Effects Of...mentioning
confidence: 99%